Estimating crustal thickness using SsPmp in regions covered by low‐velocity sediments: Imaging the Moho beneath the Southeastern Suture of the Appalachian Margin Experiment (SESAME) array, SE Atlantic Coastal Plain. Issue 18 (29th September 2016) - Parker Jr., E. Horry; Hawman, Robert B.; Fischer, Karen M.; Wagner, Lara S.
Abstract: Deconvolved waveforms for two earthquakes ( Mw : 6.0 and 5.8) show clear postcritical SsPmp arrivals for broadband stations deployed across the coastal plain of Georgia, allowing mapping of crustal thickness in spite of strong reverberations generated by low‐velocity sediments. Precritical SsPmp arrivals are also identified. For a basement in which velocity increases linearly with depth, a bootstrapped grid search suggests an average basement velocity of 6.5 ± 0.1 km/s and basement thickness of 29.8 ± 2.0 km. Corresponding normal‐incidence Moho two‐way times (including sediments) are 10.6 ± 0.6 s, consistent with times for events interpreted as Moho reflections on coincident active‐source reflection profiles. Modeling of an underplated mafic layer ( Vp  = 7.2–7.4 km/s) using travel time constraints from SsPmp data and vertical‐incidence Moho reflection times yields a total basement thickness of 30–35 km and average basement velocity of 6.35–6.65 km/s for an underplate thickness of 0–15 km. Key Points: Unstacked broadband waveforms show clear postcritical SsPmp arrivals over low‐velocity sediments of the Georgia coastal plain Precritical SsPmp arrivals are also visible Average basement Vp (6.5–6.6 km/s) allows for, but does not require, high Vp in the lower crust associated with Mesozoic underplating